A Plague of the State and the Church: A Local Response to the Moravian Enterprise - Petterson, Christina (Journal of Moravian history, 2016)
In 1755 the Lutheran Pastor Johann Gottlob Seidel published his polemical text Haupt-Schlüssel zum Herrnhutischen Ehe-Sacrament. The publication consisted of a number of Count Zinzendorf's sermons to the married choirs in Herrnhut, Herrnhaag and Marienborn, with an introduction and running commentary by Seidel. The introduction is the point of departure of this article because Seidel's vehement criticism of Zinzendorf's business practices provides an insight into the effects of the emerging global economy on local industry. By shifting Seidel's emphasis from marriage to the choir structure of the community, this article will demonstrate how the Moravians took part in these processes.